Seamless Integration of the Coastal Ocean in Global Marine Carbon Cycle Modeling. (26th August 2022) - Mathis, M.; Logemann, K.; Maerz, J.; Lacroix, F.; Hagemann, S.; Chegini, F.; Ramme, L.; Ilyina, T.; Korn, P.; Schrum, C.
Abstract: We present the first global ocean‐biogeochemistry model that uses a telescoping high resolution for an improved representation of coastal carbon dynamics: ICON‐Coast. Based on the unstructured triangular grid topology of the model, we globally apply a grid refinement in the land‐ocean transition zone to better resolve the complex circulation of shallow shelves and marginal seas as well as ocean‐shelf exchange. Moreover, we incorporate tidal currents including bottom drag effects, and extend the parameterizations of the model's biogeochemistry component to account explicitly for key shelf‐specific carbon transformation processes. These comprise sediment resuspension, temperature‐dependent remineralization in the water column and sediment, riverine matter fluxes from land including terrestrial organic carbon, and variable sinking speed of aggregated particulate matter. The combination of regional grid refinement and enhanced process representation enables for the first time a seamless incorporation of the global coastal ocean in model‐based Earth system research. In particular, ICON‐Coast encompasses all coastal areas around the globe within a single, consistent ocean‐biogeochemistry model, thus naturally accounting for two‐way coupling of ocean‐shelf feedback mechanisms at the global scale. The high quality of the model results as well as the efficiency in computational cost and storage requirements proves this strategy a pioneering approach for global high‐resolution modeling. We conclude that ICON‐Coast represents a new tool to deepen our mechanistic understanding of the role of the land‐ocean transition zone in the global carbon cycle, and to narrow related uncertainties in global future projections. Plain Language Summary: The coastal ocean is an area hardly taken into account by current climate change assessment activities. Yet, its capacity in carbon dioxide (CO2 ) uptake and storage is crucial to be included in a science‐based development of sustainable climate change mitigation and adaptation strategies. Earth system models are powerful tools to investigate the marine carbon cycle of the open ocean. The coastal ocean, however, is poorly represented in global models to date, because of missing key processes controlling coastal carbon dynamics and too coarse spatial resolutions to adequately simulate coastal circulation features. Here, we introduce the first global ocean‐biogeochemistry model with a dedicated representation of the coastal ocean and associated marine carbon dynamics: ICON‐Coast. In this model, we globally apply a higher resolution in the coastal ocean and extend the accounted physical and biogeochemical processes. This approach enables for the first time a consistent, seamless incorporation of the global coastal ocean in model‐based Earth system research. In particular, ICON‐Coast represents a new tool to deepen our understanding about the role of the land‐ocean transition zone in the global climate system, and to narrow related uncertainties in possible and plausible climate futures. Key Points: We introduce the first global ocean‐biogeochemistry model with a dedicated representation of coastal carbon dynamics We globally apply a grid refinement in the coastal ocean to better resolve regional circulation features, including ocean‐shelf exchange We explicitly incorporate key physical and biogeochemical processes controlling coastal carbon dynamics